Fatores críticos e capacidades dinâmicas para o desenvolvimento de inovações orientadas para sustentabilidade: proposta e análise de um framework - Rodrigues, Bruna Cavalcanti Barros (2020)
Although the literature points to the importance of organizations developing sustainable- oriented innovation, little is known about the relevance and influence of dynamic capabilities (CDs) and critical factors (CF) to develop these innovations. This research aims to develop a framework that relates dynamic capabilities (DC) with sustainable-oriented innovation based on critical factors (FC). For that, a systematic literature review (RSL) was first performed, where it was possible to characterize the types of SOI, as well as the DC and their respective FC. The SOIs identified were eco-innovation, social innovation, and sustainable-oriented innovation. The identified DCs were: absorptive, environmental, competence and the ability for innovation, resource integration, organizational, networking, and technological. After identifying the DCs, 14 FCs related to the aforementioned capabilities were mapped based on the literature. These elements were fundamental for the development of the theoretical framework. Then, this framework was applied and refined through a case study in two manufacturing units of a footwear multinational. Of the seven dynamic capabilities presented in the theoretical framework, three had a high influence on the development of SOIs (environmental, resource integration, and technological capability) of goods / services, processes and technologies. Absorptive, organizational and networking capabilities have a moderate influence on goods / services, processes, technological, and organizational innovations. The moderate influence of these capabilities in sustainable-oriented innovation can be due to the absence of certain CFs or the non-structuring of these factors in the organization. The empirical results also revealed two CFs "waste management (related to environmental DC)" and "reputation (related to organizational DC)", not listed in the studied literature. Based on the results, eight propositions were proposed that can guide future research. This research advances in the literature since it relates in a framework constructs not addressed in an integrated way in the literature. Therefore, the framework can be considered a representation of the state of the art on the subject, and can be useful for companies and managers who want to drive and develop sustainable-oriented innovation.